Chromium(VI) Ion Removal from Solution by Polyaniline/Pumice Composite - GOK, AYSEGUL; GODE, FETHIYE; ESENCAN TURKASLAN, BANU (Asian Journal of Chemistry, 2010)
The adsorption of Cr(VI) onto polyaniline/pumice(PAn/Pmc) composite has been investigated by using a batch method at room temperature and its adsorption properties was compared with PAn and Pmc. Cr(VI) adsorption was studied under different conditions (pH, time, initial Cr(VI) ion concentration, adsorbent amount and temperature) on PAn, Pmc and PAn/Pmc. The results of adsorption were fitted to both the Langmuir and Freundlich models and coefficients indicated favourable adsorption of Cr(VI) on the adsorbents. Adsorption of Cr(VI) solution was in order : PAn > PAn/Pmc > Pmc. Data from this study proved that the Cr(VI) adsorption from aqueous solutions amounts by polyaniline and its composite with pumice. The adsorption capacity of Pmc, PAn and PAn/Pmc were found as 0.42, 111.56, 0.77 and 0.05, 0.44, 0.18 for Freundlich and Langmuir adsorption isotherms, respectively. The thermodynamic parameter (free energy change, ΔG) for the adsorption has been evaluated. The sorption of Cr(VI) onto the adsorbents followed reversible first-order rates kinetics.